A Density Functional Theory Study on the Acid‐Catalyzed Transesterification Mechanism for Biodiesel Production from Waste Cooking Oils. (14th December 2018) - Li, Tan; Zhang, Xiaochao; Zhang, Changming; Li, Rui; Liu, Jianxin; Zhang, Hui; Han, Peide; Zheng, Zhanfeng; Fan, Caimei
Abstract: The acid‐catalyzed transesterification reaction has been one of the most effective methods to produce biodiesel, especially from waste cooking oils (WCO) with high contents of water and free fatty acids (FFA). However, in the acid‐catalyzed processes, the H + action mechanism and the controlling step of the reaction rate have been ambiguous. To clearly understand the reaction process, the DMol3 module based on the density functional theory (DFT) was employed to investigate the acid (H + ‐)‐catalyzed transesterification mechanism of methanol and oleic acid monoacylglycerol (OAM). The one step transesterification without a catalyst and the feasible paths of SN2 (substitution nucleophilic bimolecular) and SN1 (substitution nucleophilic unimolecular) reaction mechanisms with H + ‐based catalysts were built as Path 1, Path 2, and Path 3, respectively. The calculated structures, thermodynamic, and kinetic data revealed that the H + ‐based catalysts could effectively reduce the activation energy for the transesterification reaction, and the Path 2 based on the SN2 reaction mechanism was the optimal reaction path. A tetrahedral intermediate (IM2‐2) could be generated with the highest active energy of 15.383 kcal mol −1, implying that there was the most stable structure of IM2‐2 as the key species in the transesterification process. Hence, the increasing decomposition rate of IM2‐2 accelerated the forward reaction in H + ‐based biodiesel processes. The calculated active energy of 15.383 kcal mol −1 was in good agreement with the kinetic data for the monoacylglycerol transesterification of 15.067 kcal mol −1 . Our calculations should provide basic and reliable theoretical data for further understanding the mechanism of transesterification of WCO to biodiesel products in the future work.